DESAIN BASIS DATA SISTEM INFORMASI AKADEMIK DI FAKULTAS TEKNIK UNIVERSITAS TADULAKO - Joefrie, Yuri Yudhaswana; Kalatiku, Protus Pieter (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2012)
Abstract- This research aims to build the academic systems information which is focused in table and inter table relation. Table design and decision of inter table relation are very important in term of creating an information system because those table and relation have influence in system performance andÂ to avoid data redundancy. Method used in this study is interview with user who involved in the system and retrieve the hardcopy needed. Normalisation is done to the third stage. The conclusion found in this research is that the amount of table used in this system are six and there is no data redundancy. Keywords: database, inter-table relation